Synthesis and biological evolution of hydrazones derived from 4-(trifluoromethyl)benzohydrazide - Krátký, Martin; Bősze, Szilvia; Baranyai, Zsuzsa; Stolaříková, Jiřina; Vinšová, Jarmila (Bioorganic & medicinal chemistry letters, 2017)
Reflecting the known biological activity of isoniazid-based hydrazones, seventeen hydrazones of 4-(trifluoromethyl)benzohydrazide as their bioisosters were synthesized from various benzaldehydes and aliphatic ketones. The compounds were screened for their in vitro activity against Mycobacterium tuberculosis, nontuberculous mycobacteria (M. avium, M. kansasii), bacterial and fungal strains. The most antimicrobial potent derivatives were also investigated for their cytostatic and cytotoxic properties against three cell lines. Camphor-based molecule, 4-(trifluoromethyl)-N'-(1,7,7-trimethylbicyclo[2.2.1]heptan-2-ylidene)benzohydrazide, exhibited the highest and selective inhibition of M. tuberculosis with the minimum inhibitory concentration (MIC) of 4 µM, while N'-(4-chlorobenzylidene)-4-(trifluoromethyl)benzohydrazide was found to be superior against M. kansasii (MIC = 16 µM). N'-(5-Chloro-2-hydroxybenzylidene)-4-(trifluoromethyl)benzohydrazide showed the lowest MIC values for gram-positive bacteria including methicillin-resistant Staphylococcus aureus as well as against two fungal strains of Candida glabrata and Trichophyton mentagrophytes within the range of ≤0.49-3.9 µM. The convenient substitution of benzylidene moiety at the position 4 or the presence of 5-chloro-2-hydroxybenzylidene scaffold concomitantly with a sufficient lipophilicity are essential for the noticeable antimicrobial activity. This 5-chlorosalicylidene derivative avoided any cytotoxicity on two mammalian cell cultures (HepG2, BMMΦ) up to the concentration of 100 µM, but it affected the growth of MonoMac6 cells.
Keywords: Animals; Hep G2 Cells; Mycobacterium tuberculosis; buněčné linie; Hydrazone; buňky Hep G2; mikrobiální testy citlivosti; Candida glabrata; Mycobacterium avium Complex; Antibacterial activity; Mycobacterium kansasii; Nontuberculous mycobacteria; hydrazony; lidé; antiinfekční látky; Mice; Anti-Infective Agents; Mycobacterium avium komplex; Cytostasis; myši; Hydrazones; Cell Line; Microbial Sensitivity Tests; Antifungal activity; Cell Survival; zvířata; viabilita buněk; 4-(Trifluoromethyl)benzohydrazide; Cytotoxicity; Humans